Concluding reflections. (1st June 2021) - Volk, Steven S.
Abstract : In October 2020, Chilean voters resoundingly elected to abandon the constitution left behind by the Pinochet dictatorship. A new charter will be written by a fully elected, gender-balanced, constitutional convention. Given that Chilean political leaders have floated the idea of jettisoning the 1980 constitution for the last 35 years, what accounts for their decisive step at this point? Summarising and reflecting on the contributions to this special issue, I argue that the October 2020 vote was, in a sense, the result of decades of popular resistance, nurtured and informed by rich and tragic historical memories and experiences. The October result demonstrated an understanding of how to mobilise and energise a huge and diverse base of popular support as well a keen awareness of how to prepare for the violence that inevitably was launched against it.